2004
DOI: 10.1128/jb.186.14.4655-4664.2004
|View full text |Cite
|
Sign up to set email alerts
|

Response ofBacillus subtilisto Nitric Oxide and the Nitrosating Agent Sodium Nitroprusside

Abstract: We examined the effects of nitric oxide (NO) and sodium nitroprusside (SNP) on Bacillus subtilis physiology and gene expression. In aerobically growing cultures, cell death was most pronounced when NO gas was added incrementally rather than as a single bolus, suggesting that the length of exposure was important in determining cell survival. DNA microarrays, Northern hybridizations, and RNA slot blot analyses were employed to characterize the global transcriptional response of B. subtilis to NO and SNP. Under b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 67 publications
(81 reference statements)
4
121
0
2
Order By: Relevance
“…Exposure of B. subtilis to either an NO bolus or the NO generator Na-nitroprusside results in PerR-mediated induction of the PerR regulon during growth under aerobic and anaerobic conditions (77). The observation that anaerobic growth in the presence of Mn 2ϩ reduces NO-induced expression of the PerR regulon while high iron levels enhance it suggests that induction is mediated by PerR-Zn 2ϩ -Fe 2ϩ .…”
Section: Perrmentioning
confidence: 82%
“…Exposure of B. subtilis to either an NO bolus or the NO generator Na-nitroprusside results in PerR-mediated induction of the PerR regulon during growth under aerobic and anaerobic conditions (77). The observation that anaerobic growth in the presence of Mn 2ϩ reduces NO-induced expression of the PerR regulon while high iron levels enhance it suggests that induction is mediated by PerR-Zn 2ϩ -Fe 2ϩ .…”
Section: Perrmentioning
confidence: 82%
“…In B. subtilis, the fur mutant has a growth defect in the presence of SNP (39). Moore et al (39) suggested that this is due to the formation of Fe-nitrosyl complexes, which leads to the release of nitroxyl anion and formation of nitrous oxide (45). The ahpC katA mutant of S. aureus was more sensitive to SNP than the wild type but less than the fur mutant.…”
Section: Discussionmentioning
confidence: 99%
“…If similar values pertain to B. subtilis, this would explain why, in the presence of both iron and manganese in the growth medium, PerR is predominantly in the peroxide-sensing PerR:Zn,Fe form. Apparently in cells grown in manganese-supplemented minimal medium (with no added iron), the intracellular level of iron is lowered sufficiently to allow the PerR:Zn,Mn form of the repressor to predominate (2,25). Yet because of the relatively higher affinity for Fe 2ϩ , a small increase in intracellular free Fe 2ϩ could shift the repressor from the PerR:Zn,Mn to the Per-R:Zn,Fe form.…”
Section: Discussionmentioning
confidence: 99%
“…In medium containing iron or iron and manganese, induction is efficient with complete derepression elicited by Ͻ100 M H 2 O 2 or by exposure to NO-generating agents. In contrast, in low iron minimal medium supplemented with manganese, the resulting PerR:Zn,Mn form of the repressor is relatively insensitive to peroxide-and NO-mediated inactivation (2,10,25).…”
mentioning
confidence: 96%